2021
DOI: 10.3390/antibiotics10080902
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Ghanaian Allium Species for Anti-Infective and Resistance-Reversal Natural Product Leads to Mitigate Multidrug-Resistance in Tuberculosis

Abstract: The bulbs of Allium species are a known source of antibacterial phytochemicals. Anti-infective, efflux pump and biofilm inhibitory activities of bulb extracts of selected Ghanaian shallots Allium cepa var aggregatum were evaluated using the HT-SPOTi assay and other whole-cell phenotypic screening techniques to determine their possible mechanisms of action. Ethanol and aqueous extracts of white A. cepa inhibited the growth of Mycobacterium smegmatis mc2 155 and Escherichia coli, respectively. The majority of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 33 publications
1
1
0
Order By: Relevance
“…However, Nemati et al ( 16 ) revealed that fresh lyophilized powder of shallot is effective against E. coli, Klebsiella , and Staphylococcus aureus (with a MIC of 3.29, 3.6, and 3.8 mg/ml, respectively). These results are further confirmed by a more recent study by Danquah et al ( 28 ), who reported that Ethanol and aqueous extracts of shallot inhibited the growth of Mycobacterium smegmatis and Escherichia coli .…”
Section: Antimicrobial Activitysupporting
confidence: 82%
“…However, Nemati et al ( 16 ) revealed that fresh lyophilized powder of shallot is effective against E. coli, Klebsiella , and Staphylococcus aureus (with a MIC of 3.29, 3.6, and 3.8 mg/ml, respectively). These results are further confirmed by a more recent study by Danquah et al ( 28 ), who reported that Ethanol and aqueous extracts of shallot inhibited the growth of Mycobacterium smegmatis and Escherichia coli .…”
Section: Antimicrobial Activitysupporting
confidence: 82%
“…Saponins extracted from A. sativum had antifungal activity against B. cinerea and Trichoderma harzianum [ 204 ]. Allium species from Ghana were reported by Danquah et al to possess anti-infective and resistance modulatory effects on selected microbial strains [ 205 ]. Allium hirtifolium was found to exhibit antimicrobial activities against E. faecalis [ 206 ].…”
Section: The Genus Alliummentioning
confidence: 99%